Psychophysiological Adaptation of International Students to Learning Abroad - Holubnycha, Liudmyla; Matsapura, Liudmyla; Miroshnik, Larysa; Hetmanets, Iryna; Kovalchuk, Olena; Khodakovska, Oksana (International Journal of Innovative Research and Scientific Studies, 2022)
The article describes the problems international students encounter during psychophysiological adaptation. As the modern higher education system is characterized by academic mobility, and international students from countries with quite different geoclimatic and cultural traditions have to undergo an adaptation period, the problem under study is topical. The study was conducted at Kharkiv National Medical University (Ukraine) in 2020/2021. The research involved 1st, 2nd and 3rd-year international students (from 50 countries). The peculiarities of international students’ psychophysiological states were assessed during the stages of initial adaptation, stable adaptation and final adaptation. This study aims to provide a comprehensive analysis of the factors of the natural and socio-pedagogical environment that affect the psychological adaptation process of international students. The present study provides new information on the acclimatization patterns of international students who study in Ukraine, as well as its functional significance on selected performance measures. General theoretical methods, research methods and methods of statistical data processing have been employed. The results reveal that the destabilizing factors that negatively affect international students’ adaptation process include frequent hypothermia, dietary changes, inadequate and irregular food intake, insufficient physical activity and excessive mental stress. Practical recommendations to decrease these negative factors are proposed.